The development of firms : an empirical study with special reference to the economic effects of taxation - Mackintosh, Athole S. (Cambridge [Eng.] : Cambridge University Press, 1963)
This book is a report of a general inquiry into the development of firms and the factors which may limit their rates of development.
Includes index
uaa 25/01/2019
Loans.
Keywords: Business enterprises; Corporations